Bilateral eventration of the diaphragm: report of a case and reviw of the literature - Gómez Ruiz Alejandro; Medina Vega Francisco Antonio; Tejeda Tapia Hector David (Instituto Nacional de Pediatría, 2014)
Introduction. Diaphragmatic eventration is a congenital malforma- tion which could result in respiratory distress. A chest X-ray, shows an elevated diaphragm. Most case reports present unilateral dia- phragmatic eventration. We report a case of an infant with bilateral diaphragmatic elevation. Case report. A 17 day old infant presented with respiratory distress. With the aid of an Xray study we diagnosed a bilateral congenital eventration of the diaphragm (BCED). A bilateral thoracotomy was performed. Discussion. Congenital diaphragmatic eventration represents 5% of all diaphragmatic pathology. There have been few reports of bilateral congenital diaphragmatic eventration. We found only nine reported cases since 1973, and only one in Mexico and Latin America. A bilateral diaphragmatic placation in our patient was successful.